2012
DOI: 10.12669/pjms.291.2944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eutectic mixture of local anesthetics cream with dorsal penile nerve block using lignocaine for circumcision in infants

Abstract: Objective: Circumcision is a commonly performed surgical procedure but choice of anesthesia remained an issue of research and debate. This study was conducted to find out the effectiveness of the eutectic mixture of local anesthetic (EMLA) cream with dorsal penile nerve block (DPNB) using lignocaine, for reduction of pain during circumcision. Methodology: This was comparative study carried out in Surgical Unit B of National Institute of Child Health Karachi, from May 2008 to October 2008. Patients under six mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…In the present study, the changes in SpO 2 were similar to the findings of Sabeen Mujeeb et al 8 who also noted a decrease in SpO 2 throughout the procedure without any statistically significant difference between both groups. Michael Holliday 34 et al who compared DPNB with lidocaine versus placebo also noted a similar decrease in SpO 2 in both groups.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the changes in SpO 2 were similar to the findings of Sabeen Mujeeb et al 8 who also noted a decrease in SpO 2 throughout the procedure without any statistically significant difference between both groups. Michael Holliday 34 et al who compared DPNB with lidocaine versus placebo also noted a similar decrease in SpO 2 in both groups.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to the finding by Butler-O’Hara et al 11 who noted significantly higher NIPS scores among the patients who had EMLA cream during lysis of adhesions and tying. However, a different observation was made by Sabeen Mujeeb et al 8 who noted significantly higher NIPS scores during crushing and cutting among patients who had DPNB with lidocaine. These differences may be attributed to interobserver variability in scoring as well as to the fact that the behavioral changes assessed in the NIPS may be affected by factors other than pain, such as hunger or discomfort due to restraint.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Lehr, V. T et al [ 15 ] also observed the largest mean difference in HR values between DPNB- and EMLA-treated infants at clamping (19±9.1 bpm) and cutting (18±9.6 bpm), although these were not significant (P = 0.13 and P = 0.18, respectively). Mujeeb Sabeen et al [ 21 ] demonstrated that the heart rate increased 12 times greater in EMLA group than the DPNB group. However, in this our study, there did not have any significant difference in analgesic efficacy between the study treatments according to the mean HR throughout the circumcision instead of several phase.…”
Section: Discussionmentioning
confidence: 99%